Metformin pre-treatment of stem cells from human exfoliated deciduous teeth promotes migration and angiogenesis of human umbilical vein endothelial cells for tissue engineering - Deng, Shiwen; Lei, Tong; Chen, Hongyu; Zheng, Huiting; Xiao, Zhuangzhuang; Cai, Shanglin; Hang, Zhongci; Xiong, Weini; Yu, Yanqing; Zhang, Xiaoshuang; Yang, Yanjie; Bi, Wangyu; et al. (Cytotherapy (Oxford, England), 2022)
Stem cells from human exfoliated deciduous teeth (SHED) play a significant role in tissue engineering and regenerative medicine. Angiogenesis is crucial in tissue regeneration and a primary target of regenerative medicine. As a first-line anti-diabetic drug, metformin demonstrates numerous valuable impacts on stem cells. This study aimed to explore metformin's impact and mechanism of action on SHED-mediated angiogenesis. First, cell proliferation; flow cytometry; osteogenic, adipogenic and chondrogenic induction; and proteomics analyses were conducted to explore the role of metformin in SHED. Subsequently, migration and tube formation assays were used to evaluate chemotaxis and angiogenesis enhancement by SHED pre-treated with metformin under co-culture conditions in vitro, and relative messenger RNA expression levels were determined by quantitative reverse transcription polymerase chain reaction. Finally, nude mice were used for in vivo tube formation assay, and sections were analyzed through immunohistochemistry staining with anti-human CD31 antibody. Metformin significantly promoted SHED proliferation as well as osteogenic, adipogenic and chondrogenic differentiation. Proteomics showed that metformin significantly upregulated 124 differentially abundant proteins involved in intracellular processes, including various proteins involved in cell migration and angiogenesis, such as MAPK1. The co-culture system demonstrated that SHED pre-treated with metformin significantly improved the migration and angiogenesis of human umbilical vein endothelial cells. In addition, SHED pre-treated with metformin possessed greater ability to promote angiogenesis in vivo. In summary, the authors’ findings illustrate metformin's mechanism of action on SHED and confirm that SHED pre-treated with metformin exhibits a strong capacity for promoting angiogenesis. This helps in promoting the application of dental pulp-derived stem cells pre-treated with metformin in regeneration engineering.